Leaf epidermis images for robust identification of plants - Da Silva, Núbia Rosa; Oliveira, Marcos William Da Silva; Filho, Humberto Antunes De Almeida; Pinheiro, Luiz Felipe Souza [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Kolb, Rosana Marta [UNESP]; Bruno, Odemir Martinez (Springer Nature, 2016)
This paper proposes a methodology for plant analysis and identification based on extracting texture features from microscopic images of leaf epidermis. All the experiments were carried out using 32 plant species with 309 epidermal samples captured by an optical microscope coupled to a digital camera. The results of the computational methods using texture features were compared to the conventional approach, where quantitative measurements of stomatal traits (density, length and width) were manually obtained. Epidermis image classification using texture has achieved a success rate of over 96%, while success rate was around 60% for quantitative measurements taken manually. Furthermore, we verified the robustness of our method accounting for natural phenotypic plasticity of stomata, analysing samples from the same species grown in different environments. Texture methods were robust even when considering phenotypic plasticity of stomatal traits with a decrease of 20% in the success rate, as quantitative measurements proved to be fully sensitive with a decrease of 77%. Results from the comparison between the computational approach and the conventional quantitative measurements lead us to discover how computational systems are advantageous and promising in terms of solving problems related to Botany, such as species identification.